Cytotoxic T Lymphocytes’ Function in an Adenovirus Infection - Al-Ukaily , Hussein Ali Mohammed; Alqaisi , Ali Abbas Sadiq; Ali , Haneen Maed; Kashkul , Saja Ali; Rasheed, Walaa Jabbar; Abood , Ali Jalal (American Journal of Biology and Natural Sciences, 2025)
Adenovirus infections pose a significant risk to immunocompromised individuals and challenge the efficacy of viral vector-based gene therapies due to strong immune responses. While the involvement of cytotoxic T lymphocytes (CTLs) in adenoviral immunity is recognized, detailed understanding of epitope-specific CD8⁺ T cell dynamics and their persistence remains limited. This study utilized BALB/c and C57BL/6 mouse models to identify immunodominant CD8⁺ T cell epitopes using ELISPOT assays targeting hexon and DNA-binding proteins of adenovirus serotype 5. The findings reveal that T cell responses peak early and remain detectable for several weeks post-vaccination, with similar responses observed between wild-type and E1-deleted vectors. Furthermore, pre-exposure to adenovirus impacted the functional clearance of viral transgenes in B-cell-deficient mice, underscoring the significance of memory T cell responses. These results highlight the critical role of CTLs in controlling adenoviral infections and have direct implications for improving adenoviral vector design, vaccination strategies, and immunotherapy in immunocompromised patients.